2022
DOI: 10.1155/2022/3752466
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Post Removal Using a Conservative Fully Guided Approach: A Dental Technique

Abstract: This report describes the usefulness of an endodontic template for the removal of a fiber post. A 40-year-old man presented with discomfort in the maxillary left canine. Clinical and radiographic examinations showed tooth #23 with a permanent core material retained with fiber post along with a persistent apical radiolucency. Among the various treatment modalities, nonsurgical root canal retreatment with fiber post removal using a conservative fully guided approach was proposed. After obtaining both the cone-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The technical workflow of the data acquisition, CAD-CAM, and clinical application of this guide system is similar to that of a traditional post removal guide. [11][12][13][14][15] However, major differences exist in the data processing steps to develop the special configurations of this guide system, as described in this technique report. There are several advantages of this design compared with the traditional one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The technical workflow of the data acquisition, CAD-CAM, and clinical application of this guide system is similar to that of a traditional post removal guide. [11][12][13][14][15] However, major differences exist in the data processing steps to develop the special configurations of this guide system, as described in this technique report. There are several advantages of this design compared with the traditional one.…”
Section: Discussionmentioning
confidence: 99%
“…Guided implantology and endodontics have emerged to provide high levels of accuracy, safety, and efficiency 9,10 . Recently, a guided technique has also been used to remove fiber‐posts 11–15 . These guide systems reported for fiber‐post removal apply the traditional design with a sleeve to guide the rotary instrument.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The guided endodontic technique can accurately remove the fiber post, and this approach is predictable. Previous studies reported successful case management of infected root canals with fiber post using endodontic static guides [20,21]. Perez et al indicated that the mean deviation between the virtual design and actual dimensions after removing the fiber post was 0 39 ± 0 14 mm coronally and 0 40 ± 19 mm apically [7].…”
Section: Discussionmentioning
confidence: 99%
“…Using the snowball technique one more publication was identified. Finally, 9 studies were included in this review [22]- [30]. Inter-reviewer reliability was calculated using Cohen's kappa (0.92 for the first round, 1 for the second round).…”
Section: A Study Selectionmentioning
confidence: 99%